Indonesian Travel Documents and the ICAO Document 9303: Principles, Security, Technology, and Infrastructure - Intan Nurkumalawati; Eva Achjani Zulfa; Muhammad Syaroni Rofii (Badan Strategi Kebijakan Hukum, 2024)
The issuance, printing, production, and distribution standards of Indonesian travel documents refer to international standards of travel documents and the Regulation of Minister of Law and Human Rights. However, significant issues have risen that the Indonesian passport holders without the bearer's signature who applied for German visa were rejected by the Embassy of Federal Republic of Germany in Jakarta. Besides, the stolen and lost Indonesian Passport policy is fragmented between the Indonesian National Police, Immigration offices and the Interpol. Using the document analysis and policy evaluation, this paper investigates the issuance standards of Indonesian travel documents under the ICAO Document 9303 about Travel Documents and the policy and management of the stolen and lost Indonesian travel documents. This study shows the Indonesian travel documents have not fully complied with the ICAO Doc 9303 in which the bearer's signature is a compulsory either in the biodata page or in additional pages. Data of stolen and lost Indonesian Passport have not been recorded in the Interpol Stolen and Lost Travel Documents (SLTD) database. We propose the infrastructure of the security, cooperation, and management of the SLTD, and all Indonesian travel documents must be redesigned and equipped with the chip features.